A STUDY ON THE EFFECT OF NEW TOLL ROAD TANJUNG PRIOK-CIKARANG FOR THE EFFICIENCY IN JAKARTA INTERNATIONAL CONTAINER TERMINAL - , SUCI SUSANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tanjung Priok Port is the main gateway of Indonesia, for both international trade and domestic trade. One of the terminals in the main port of Indonesia and as the main gate of international trade is Jakarta International Container Terminal (JICT). JICT is the biggest and busiest container terminal in Indonesia. Currently, the high flow of goods from and to the terminal is still dominated by road transport. But, this condition is not supported by well transportation system. In Jakarta there is no special road for goods transportation. It is still being mixed with the public road for passengersâ transportation. It causes congestion and delay from the long queue occurs inside and outside the terminal. It also makes increasing travel time that causes additional cost for the distribution of goods and transport cost become more expensive. One of the alternatives to overcome this problem is by providing the new toll road Cibitung - Cilincing that has 34.30 km length. It is expected that can reduce the existing road load and accelerate the flow and distribution of goods from Cikarang â Tanjung Priok. Then, travel time and dwelling time from Cikarang â Tanjung Priok and vice versa can be more efficient and controlled. To conduct this research, some methodologies that used are conducting surveys: interviews to the truck driver, field observation about traffic volume, road capacity and travel time. Besides, data collection such as traffic cargos, terminal facilities and study literature are needed for supporting the primary data, Based on data analysis, this new toll road only has 2 segments